Strain-induced deterministic moiré superlattices in 2D materials - Yu-Mi Wu; Sihun Lee; Yufeng Xi; Stephen D. Funni; Saif Siddique; Natalie L. Williams; Giovanni Sartorello; Hesam Askari; Judy J. Cha (Proceedings of the National Academy of Sciences, 2026)
Moiré superlattices in two-dimensional (2D) materials have been realized through lattice mismatch or rotational misalignment between atomic layers. Here, we extend moiré formation to heterostrain in transition metal dichalcogenides using a scalable process that deterministically induces strain to 2D materials. By applying patterned thin-film stressors and probing the resulting atomic structure with scanning transmission electron microscopy, we directly resolve the induced heterostrain, lattice deformations, and stacking variations that produce the moiré superlattice. We find that uniaxial and biaxial heterostrain give rise to distinct moiré patterns, including stripes and distorted hexagonal geometries. Such reconstruction creates in-plane polar distortions at the domain boundaries of the moiré superlattice in MoS 2 , producing polarization textures different from those induced by twisting. The deterministic construction of moiré patterns using a well-established scalable process opens opportunities to design new moiré geometries in 2D materials.